POOR PROGNOSIS PREDICTOR IN ISCHEMIC HEART DISEASE PATIENTS WITH CONFIRMED HEMODYNAMICALLY SIGNIFICANT CORONARY ARTERY ATHEROSCLEROSIS IN THE DYNAMICS OF LONG OBSERVATION - L. N. Yakovleva (Zaporožskij Medicinskij Žurnal)
The purpose of the study - to determine the clinical-anamnestic, instrumental parameters, and genetic factors, that that determine the development of adverse cardiovascular events (ACVE) in patients with ischemic heart disease (IHD) with a verified hemodynamically significant coronary artery (CA) atherosclerosis at long follow-up.